PERANAN DUKUNGAN PENDAMPING DAN KEBIASAAN MAKAN PASIEN KANKER SELAMA MENJALANI TERAPI - Caesandri, Stefana Danty Putri; Adiningsih, Sri (Media Gizi Indonesia, 2017)
Cancer patients had a decrease in appetite which leads to weight loss and nutritional status due to the cancer itself or the side effect of therapy. The existence of family support as a chaperone has an important role in the nutritional fulfillment of cancer patients as a form of instrumental support. The aim of this research was to identify the role of family support and the eating habit of cancer patients during undergo a therapy while living in Rumah Singgah Sasana Marsudi Husada, Cancer Foundation Indonesia branch of East Java. This was a descriptive research with cross sectional study design. The sample was total population of cancer patients for about 20 people. Data collected by interview including the role support from chaperone and eating habit of cancer patients which includes the type and frequency of eating. The type and frequency of eating were categorized according to Healthy Eating Index. This research found that 15% respondents who have good diet obtain the good role of chaperone support and respondents who included as diet needs improvement obtain the role of good chaperone support (30%) and quiet chaperone support (35%). The conclusion is that eating habit of cancer patients not only influenced by the role of chaperone support, but also influenced by characteristics of cancer patients. Cancer patients should improve their food intake, especially fruit, vegetable, and milk intake to achieve good diet. Keywords: eating habits, cancer patient, role of chaperone support, therapy